The LSQ Dataset: Querying for Queries - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Automatic SPARQL Benchmark Generation using FEASIBLE - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LANCE: Piercing to the Heart of Instance Matching Tools - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

LANCE: A Generic Benchmark Generator for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Enhancing Dataset Quality using Keys - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Interlinking: Performance Assessment of User Evaluation vs. Supervised Learning Approaches - M. Hassan, Mofeed; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Workshop on Linked Data on the Web, LDOW 2015, co-located with the 24th International World Wide Web Conference {(WWW} 2015), Florence, Italy, May 19th, 2015)

Pushing the Limits of Instance Matching Systems: A Semantics-Aware Benchmark for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

CubeViz: Exploration and Visualization of Statistical Linked Data - Martin, Michael; Abicht, Konrad; Stadler, Claus; Ngonga Ngomo, Axel-Cyrille; Soru, Tommaso; Auer, Sören (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

ROCKER: A Refinement Operator for Key Discovery - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

GERBIL: General Entity Annotator Benchmarking Framework - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Baron, Ciro; Both, Andreas; Brümmer, Martin; Ceccarelli, Diego; Cornolti, Marco; Cherix, Didier; Eickmann, Bernd; Ferragina, Paolo; Lemke, Christiane; et al. (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; García-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; Westphal, Patrick; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene - Böhm, Julian; Bellec, Matthieu; Mortessagne, Fabrice; Kuhl, Ulrich; Barkhofen, Sonja; Gehler, Stefan; Stöckmann, Hans-Jürgen; Foulger, Iain; Gnutzmann, Sven; Tanner, Gregor (Physical Review Letters)

Compounding approach for univariate time series with nonstationary variances - Schäfer, Rudi; Barkhofen, Sonja; Guhr, Thomas; Stöckmann, Hans-Jürgen; Kuhl, Ulrich (Physical Review E)

Optimierung von Wasserbehältern in einem Wasserversorgungssystem mittels einer Kombination aus Netzreduktion, mathematischer Optimierung und hydraulischer Simulation - Hallmann, Corinna

Quantum walk coherences on a dynamical percolation graph - Elster, Fabian; Barkhofen, Sonja; Nitsche, Thomas; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Scientific Reports)

20 years of learning with the World Wide Web - technology and education in dialogue

Learn with, through and {\ "about the WWW - Keil, Reinhard; Selke, Harald

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Development of a structured process of interaction design for {\ "u} r nat ü local user interfaces - Klompmaker, Florian

Empirical validation of design patterns - Schild, Christian; Petrausch, Vanessa (Human and Computer 2015 - Proceedings)
Patterns serve to codify design knowledge. By embedding them in a hypothesis-driven design, it is possible to develop them further into sample languages. For this it is necessary to resolve the underlying conflicts in the form of design hypotheses and to validate them empirically in order to enable further use and generalization. In this article, an experiment is presented that describes this procedure and demonstrates the interplay between theory formation and codification of design knowledge using two examples.